2018
DOI: 10.3389/fmolb.2018.00068
|View full text |Cite
|
Sign up to set email alerts
|

Fumarase: From the TCA Cycle to DNA Damage Response and Tumor Suppression

Abstract: Fumarase is an enzyme of the tricarboxylic acid (TCA) cycle in mitochondria, but in recent years, it has emerged as a participant in the response to DNA double strand breaks (DSBs) in the nucleus. In fact, this enzyme is dual-targeted and can be also readily detected in the mitochondrial and cytosolic/nuclear compartments of all the eukaryotic organisms examined. Intriguingly, this evolutionary conserved cytosolic population of fumarase, its enzymatic activity and the associated metabolite fumarate, are requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 100 publications
(133 reference statements)
1
37
0
Order By: Relevance
“…The observation that no UL had two SNVs/indels, points to an initial FH mutation (SNV/indel or CNV) in a progenitor cell which then increased the probability for a CN-loss in descendent cells. Fumarase is known to play a role in response to double strand-breaks (DSB) by activating the non-homologous end joining (NHEJ) mechanism [ 56 ]. When the NHEJ pathway is inactivated the DSB are repaired by more error prone mechanisms, like microhomology-mediated end joining, which can lead to deletions.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that no UL had two SNVs/indels, points to an initial FH mutation (SNV/indel or CNV) in a progenitor cell which then increased the probability for a CN-loss in descendent cells. Fumarase is known to play a role in response to double strand-breaks (DSB) by activating the non-homologous end joining (NHEJ) mechanism [ 56 ]. When the NHEJ pathway is inactivated the DSB are repaired by more error prone mechanisms, like microhomology-mediated end joining, which can lead to deletions.…”
Section: Discussionmentioning
confidence: 99%
“…While it seems plausible that the reduction of MDH2 is linked to reduced mitochondrial capacity, the increase in FH may be related to another mechanism. It has been recently demonstrated that the role of FH is not only to produce reducing equivalents as part of the TCA cycle, but it also plays a role in DNA damage response; recently, telomeres length and DNA damage response in non‐dividing cardiomyocytes have been connected to cardiomyopathy, thus suggesting that FH serum level could be associated to cardiac involvement in DMD . Another protein increasing with age was RELB, which is a member of the alternative NF‐ÎșB complex and is known to promote mitochondrial biogenesis and transition from a glycolytic towards an oxidative metabolism in muscle fibres .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FH is also involved in the response to the nuclear DNA double strand breaks [108] to maintain genomic stability [109]. Consequently, FH inactivation takes part in cancer development by inducing a loss of genome integrity.…”
Section: Fumarate Hydratasementioning
confidence: 99%